Monolayered Ti3C2O/(001) TiO2 photocatalyst with Schottky junction and active facets for hydrogen production. (12th August 2022) - Chen, Lu; Qiang, Taotao; Qiu, Boqiang; Yu, Mengdi; Ren, Longfang
Abstract: Monolayered Ti3 C2 O hybrid (001) TiO2 (Ti3 C2 O/(001) TiO2 ) photocatalyst was synthesized via a facile hydrothermal subsequent annealing method. The Schottky junction was constructed in situ by regulating surface functional groups, exposing highly active facets, and controlling structural dimension. Among the composite, monolayered Ti3 C2 O nanosheets acted as the electron reservoir to effectively separate the photogenerated electrons/holes. The exposure of the (001) facet largely improved the catalytic activity and surface energy of the TiO2 material. Through the well-planned triple modifications, the highest activity of photocatalytic hydrogen evolution is 13.63 times than the contrast. In this work, excellent photocatalytic material with Schottky junction was prepared by structural modification and in-situ oxidation of Ti3 C2 Tx (Mxene), which revealed considerable reference values for expanding the application scope and modification methods of Mxene material. Graphical abstract: Image 1 Highlights: Monolayered Ti3 C2 O hybrid (001) TiO2 photocatalyst was synthesized via hydrothermal post-annealing method. The optimal sample showed the vigorous production rate of 749.95 μmol/(g.h). Crystal facet, structural dimension and surface groups adjusting were applied for modification.